Parasites du Dieu Comptables, financiers et commerçants dans la Délos hellénistique - Chankowski, Véronique (Bibliothèque des Écoles françaises d'Athènes et de Rome (BEFAR), 2019)
Freed from Athenian guardianship in 314 BCE, at a time of geopolitical changes which marked the beginnings of the Hellenistic period in the Aegean world, Delos gradually built up its political and economic independence. The Delian community redefined, during the third and second centuries, the central place that the island had constantly occupied in the economic, financial and cultural flows of the Mediterranean. This study is mainly based on epigraphic accounting sources, including more than five hundred accounts and engraved inventories that were visible in the sanctuary of Apollo, but also on numismatic sources and archaeological remains on the seafront, in order to re-consider the question of Delos' place in the Hellenistic economy. Far from being an exception to be excluded from serialized comparisons, the Delian documentation is indicative of Aegean economic situations and demonstrates the capacities of the Greek communities to adapt to change in troubled times. Behind the figures engraved on the stone appear human communities and societies whose economic activities shed new light on the history of this part of the Mediterranean.